Ultrasound-Activated Bioresorbable Osteosynthesis in the Treatment of Craniosynostosis. Issue 1 (January 2021) - Chen, Youbai; Niu, Zehao; Zhang, Haizhong; Zhang, Qixu; August, Meredith; Han, Yan
Abstract : Abstract: The purpose of this study is to estimate the incidence of fixation-related complications following ultrasound-activated biodegradable osteosynthesis (UBO) in the treatment of craniosynostosis. The authors searched MEDLINE, PubMed, Embase, Google Scholar, and Cochrane Library from January 2005 to January 2020 for clinical studies reporting the use of UBO for fixation in the treatment of craniosynostosis. The primary outcome was the incidence of fixation-related complications, including unstable fixation; swelling, plate visibility, or palpability; infection; inflammation, sinus formation, and discharge; implant exposure; reoperation or implant removal. The pooled incidence rates were estimated using random-effects models. Of 155 studies identified, 10 were included, representing 371 patients. Forty-six (12.4%) patients presented fixation-related complications. The incidence rates of swelling/visibility/palpability, infection, and reoperation/implant removal were pooled based on the available data. The pooled incidence rate of chronic swelling/visibility/palpability was 0.21 (95% confidence interval [CI], 0.05–0.43). Sensitivity analysis by omitting the outlier study demonstrates that the incidence of swelling/visibility/palpability was 0.07 (95% CI, 0.04–0.11). The pooled incidence rate of infection and reoperation/implant removal was 0.07 (95% CI, 0.01–0.16) and 0.04 (95% CI, 0.01–0.09), respectively. Results show that although UBO can provide stable fixation, chronic swelling/visibility/palpability, infection, and reoperation for removal are not uncommon. Based on the literature, the authors recommend judicious use of UBO in patients with large frontorbital advancement and in the area of the coronal suture or other sites with thin overlying skin/subcutaneous tissue. The high possibility of chronic swelling/palpability/visibility during degradation, needs to be discussed preoperatively. Abstract : Supplemental Digital Content is available in the text